2016
DOI: 10.3389/fpls.2016.00598
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent Exon-Intron Structural Changes in the APETALA1/FRUITFULL, SEPALLATA, AGAMOUS-LIKE6, and FLOWERING LOCUS C MADS-Box Gene Subfamilies Provide New Insights into Their Evolution

Abstract: AP1/FUL, SEP, AGL6, and FLC subfamily genes play important roles in flower development. The phylogenetic relationships among them, however, have been controversial, which impedes our understanding of the origin and functional divergence of these genes. One possible reason for the controversy may be the problems caused by changes in the exon-intron structure of genes, which, according to recent studies, may generate non-homologous sites and hamper the homology-based sequence alignment. In this study, we first p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 97 publications
2
20
0
2
Order By: Relevance
“…A survey of the recently released Petunia axillaris and Petunia inflata genome sequences (Bombarely et al, 2016) indicated that these sequences represent the total number of SEP/ AGL6 genes in petunia (Supplemental Table 1). Several detailed and robust phylogenetic studies of the SEP family (Zahn et al, 2005;Yu et al, 2016) as well as the more limited phylogenetic analysis presented here ( Figure 1F), identified FBP2 as the sole SEP3 ortholog in petunia, meaning that the petunia SEP3 clade contains only one member as in Arabidopsis. Petunia FBP5 and PMADS12 (PM12) were shown to be the closest relatives of SEP1 and SEP2, with the FBP5/PM12 and SEP1/SEP2 paralogous pairs originating from independent gene duplications in the lineages leading to petunia and Arabidopsis, respectively.…”
Section: Petunia Sep/agl6 Expression Analysis and Mutant Identificationmentioning
confidence: 55%
See 1 more Smart Citation
“…A survey of the recently released Petunia axillaris and Petunia inflata genome sequences (Bombarely et al, 2016) indicated that these sequences represent the total number of SEP/ AGL6 genes in petunia (Supplemental Table 1). Several detailed and robust phylogenetic studies of the SEP family (Zahn et al, 2005;Yu et al, 2016) as well as the more limited phylogenetic analysis presented here ( Figure 1F), identified FBP2 as the sole SEP3 ortholog in petunia, meaning that the petunia SEP3 clade contains only one member as in Arabidopsis. Petunia FBP5 and PMADS12 (PM12) were shown to be the closest relatives of SEP1 and SEP2, with the FBP5/PM12 and SEP1/SEP2 paralogous pairs originating from independent gene duplications in the lineages leading to petunia and Arabidopsis, respectively.…”
Section: Petunia Sep/agl6 Expression Analysis and Mutant Identificationmentioning
confidence: 55%
“…Interestingly, the AGL6, SEP, and AP1/SQUA subfamilies together compose a monophyletic superclade within the MADS-box family (further referred to as the AP1/SEP/AGL6 superclade), suggesting a common ancestral origin predating the angiosperm/gymnosperm divergence, although the evolutionary relationship between the different subfamilies had not been completely resolved (Purugganan et al, 1995;Purugganan, 1997;Becker and Theissen, 2003). A more recent phylogenetic analysis based on exon/ intron structural changes suggests that AGL6 genes are sister to both SEP and AP1 subfamilies (Yu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The relationships between the major clades of the plant MADS-box genes have already largely been inferred in various phylogenetic and evolutionary studies (Becker and Theissen, 2003;Martinez-Castilla and Alvarez-Buylla, 2003;Nam et al, 2003Nam et al, , 2004Nam et al, , 2005Gramzow et al, 2012Gramzow et al, , 2014Smaczniak et al, 2012;Ruelens et al, 2013;Sun et al, 2014;Yu et al, 2016b) (Figure 1B). However, these studies cannot fully resolve some of the deepest nodes of the MADS-box gene tree.…”
Section: Introductionmentioning
confidence: 99%
“…For clarity, we have summarized the current notion of evolutionary relationships between the major clades of the MADS-box gene family (Figure 2a) based on numerous studies (Becker and Theissen, 2003; Martinez-Castilla and Alvarez-Buylla, 2003; Nam et al, 2003; Nam et al, 2004; Nam et al, 2005; Smaczniak et al, 2012; Gramzow and Theissen, 2013; Kim et al, 2013; Ruelens et al, 2013; Gramzow et al, 2014; Sun et al, 2014; Yu et al, 2016). Note that we have named the hypothesized common ancestral genes of S QUA -, F LC - and T M8 - like genes as SFT for convenience (the abbreviation SFT will be used later in this study).…”
Section: Resultsmentioning
confidence: 99%